Economic analysis of fish hatchery operations in Ogun State, Nigeria - Olaoye Olalekan Jacob; Oke Abdulfatai Olubukola (Advances in Aquaculture and Fisheries Management, 2020)
This paper examines the cost and returns, and the determinants of fish hatchery operations in agricultural extension zones of Ogun state. The simple random sampling method was used in selecting 120 fish hatchery operators out of 388 registered ones using multi-stage sampling techniques. The primary data were collected in 2010 production season with the aid of well-structured, validated and pre-tested interview guides, administered through face to face interview and direct observations so as to elicit information from the fish breeders. The data collected were analyzed using descriptive statistics and budgeting technique. The mean total income of N1,088,933.3, N1,072,133.3, N1,122,166.7 and N976,151.3 were generated on sales of fish seeds in the zones, respectively. The Benefit-Cost ratio of 1.4, 2.1, 2.6 and 2.8 in the four zones, respectively indicated that fish hatchery operations were profitable and viable enterprises. Poor marketing, poor genetic brood stocks, high inflation rate in the economy, poor infrastructural facilities and lack of finance were the major constraints hindering fish seeds production and development. Hence, hatchery operations are profitable and viable enterprises. There is a need for the establishment of brood stock banks to ensure genetically improved fish seed availability, provision of infrastructural facilities by the government and improve marketing strategy for fish seed.